PROGRAM SERTIFIKASI DAN KOMITMEN GURU: APLIKASI REGRESSION DISCONTINUINITY (RDD) - Suardi, Wahdi; Yusuf, Suhendra (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2020)
One way to increase teacher quality is through teacher certification program to ensure that teachers have sufficient competencies required for teaching. Competent teachers then should be rewarded by a proper raise in salary. Since teacher wage is now relatively higher thand before, teacher would provide more effort in order to keep their commitment.This study aims to empirically test the impact of the teacher certification program on teacher’s commitment. A total of 449 respondents teachers in Bandung were selected by a stratified random sampling method. Respondents were asked to rate items using a five-point Likert type scales (strongly disagree to strongly agree). The data were gathered using a questionnaire that has been tested for its validity and reliability. The regression-discontinuity design (RD) was used to test the hypotheses on teacher commitment’s difference between certified and uncertified teacher. The findings conclude